2017
DOI: 10.17222/mit.2015.348
|View full text |Cite
|
Sign up to set email alerts
|

A review of the surface modifications of titanium alloys for biomedical applications

Abstract: Dental implants are mechanical components that are used to restore the mastication (chewing) function and/or aesthetic appeal because of tooth loss or degradation. They are affixed (screwed) into the upper or lower jaw and act as a base for single or bridge-type tooth replacements. They are mostly manufactured from titanium alloys. The surface integrity of the manufactured implant may have a significant effect on the functioning and success of the implant. A systematic review is described on the effect of engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
(63 reference statements)
0
11
1
1
Order By: Relevance
“…However, Ra values were lower than those found by us, but this could be attributed to the various particles size, the shape or hardness of the blasting material [40]. Overall, it is assumed that the surface roughness increases with increasing ceramic particles size [43]. The surface roughness can be divided into three levels: macro-roughness (Ra ~ 10 µm), micro-roughness (Ra ~ 1 µm), and nano-roughness (Ra < 200 nm) [44,45].…”
Section: Resultsmentioning
confidence: 93%
“…However, Ra values were lower than those found by us, but this could be attributed to the various particles size, the shape or hardness of the blasting material [40]. Overall, it is assumed that the surface roughness increases with increasing ceramic particles size [43]. The surface roughness can be divided into three levels: macro-roughness (Ra ~ 10 µm), micro-roughness (Ra ~ 1 µm), and nano-roughness (Ra < 200 nm) [44,45].…”
Section: Resultsmentioning
confidence: 93%
“…However, implant surface characteristics (including surface topography, energy, chemistry, and roughness) also play significant role in enhancing osseointegration and BIC. [ 19 23 24 ] Studies have reported that increasing surface roughness of implants favors osteoblastic proliferation, collagen synthesis, and expression of integrin in the extracellular matrix, thereby improving the mechanisms associated with osseointegration. [ 25 ] In this regard, some studies placed localized organic and inorganic osteogenic coatings on implant surfaces in an attempt to improve implant surface activity and osseopromotive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Albrektsson and Wennerberg[ 22 ] stated that the surface properties of any implant biomaterial are reported to play a crucial role in promoting enhanced in vivo biological response and is one of the key parameters influencing osseointegration according to and several other researchers. [ 19 35 36 37 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations